Efforts to Improve Fine Motor Abilities through Collage Activities in Early Childhood - Wahyuni Nur Cahyawati; A. Zulkarnain Ali; Nurhafit Kurniawan (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to improve fine motor abilities in early childhood through structured collage activities as part of a learning intervention. Fine motor skills are essential for early childhood development, particularly in supporting hand–eye coordination, muscle control, and readiness for academic tasks such as writing and drawing. The research employed Classroom Action Research (CAR), conducted in two cycles, each consisting of four stages: planning, implementation, observation, and reflection. The research subjects were 15 early childhood learners identified as experiencing delays in fine motor development. Data collection techniques included direct observation, documentation, and pre-test and post-test assessments to measure changes in children’s fine motor performance. The results of the study indicate a notable improvement in children’s fine motor abilities after the implementation of collage activities. In the first cycle, only 51.67% of children achieved the categories of “expected development” and “very good development.” After revising the learning strategies and optimizing the use of collage materials in the second cycle, this percentage increased significantly to 83%. The findings demonstrate that collage activities effectively stimulate fine motor muscles, enhance hand–eye coordination, and improve children’s concentration and accuracy in completing tasks. In addition, collage activities contribute positively to children’s creativity, independence, and engagement in learning. Overall, collage activities are proven to be an effective, enjoyable, and easily implemented learning strategy for improving fine motor skills in early childhood education. The study recommends the integration of collage-based activities into daily learning practices to support optimal motor development in young children.